Characteristics and Motivational Factors of American Equine Journalists - Zoe B Bowden; Ricky W Telg; Lisa K Lundy (Journal of Applied Communications, 2022)
The purpose of this study was to identify the demographic characteristics, career motivations, and professional development of American equine journalists. An online survey was distributed to equine journalists identified through their professional organizational membership. Descriptive statistics were used to analyze the data. Equine journalists were found to be predominately female, Caucasian, and averaged 53 years old. Nearly half were exposed to the equine industry prior to their career and have been working in the industry for over 15 years. Respondents were well educated and were most motivated towards their career as an equine journalist because of their interest in horses. Over 70% of equine journalists in this study participated in one to 10 professional developments in the last year, with social media management as the most frequently reported topic. Other frequently reported topics were marketing, journalistic writing, and magazine publication. Recommendations for practice include recruiting agricultural communications minor or certificate students from specialized programs such as animal science, equine science, equine studies, or livestock. Future research should consider the influence of pre-career experiences on equine journalist career motivations and skill development.
Keywords: equine; journalism; horse